CURRENT MATTERS OF STATE MANAGEMENT AND PUBLIC ADMINISTRATION TEACHING IN GEORGIA (Globalization and Business, 2018)
State Management and Public Administration Teaching is an actual matter of all civilized countries. Educated state officials who have profound knowledge in these subjects are more effective than public servants who have received the general education. Performance at work and decisions made by the effective public servants are directly reflected on country’s success. Thus, different countries more or less successfully teach   State   Management   and   Public   Administration   at various universities (or different public training centers). It is considered that the money spent by the state is much less than the impact received from learning.In  this  work  we  are  trying  to  briefly  overview  the international   experience   and   based   on   this   reveal   the effective teaching tools. Also, we present the possible ways to measure the efficiency of training. The work is focusing on the approaches and challenges of new public management, which require constant improvement in management.  Therefore, it is necessary to update the teaching approaches to the State Management and Public Administration periodically.In addition, the work is analyzing the current condition of  state  management  and  public  administration  teaching in Georgia. Based on the public sector reform progress and produced analysis the tasks for improving the teaching approaches is introducing.